The Evolving Understanding of the Molecular and Therapeutic Landscape of Pancreatic Ductal Adenocarcinoma - Ashleigh Parkin; Jennifer Man; Angela Chou; Adnan M Nagrial; Jaswinder Samra; Anthony J Gill; Paul Timpson; Marina Pajic (Diseases, 2018)
Pancreatic cancer is the third leading cause of cancer-related deaths, characterised by poor survival, marked molecular heterogeneity and high intrinsic and acquired chemoresistance. Only 10⁻20% of pancreatic cancer patients present with surgically resectable disease and even then, 80% die within 5 years. Our increasing understanding of the genomic heterogeneity of cancer suggests that the failure of definitive clinical trials to demonstrate efficacy in the majority of cases is likely due to the low proportion of responsive molecular subtypes. As a consequence, novel treatment strategies to approach this disease are urgently needed. Significant developments in the field of precision oncology have led to increasing molecular stratification of cancers into subtypes, where individual cancers are selected for optimal therapy depending on their molecular or genomic fingerprint. This review provides an overview of the current status of clinically used and emerging treatment strategies, and discusses the advances in and the potential for the implementation of precision medicine in this highly lethal malignancy, for which there are currently no curative systemic therapies.